Effect of fluid flow-induced shear stress on the behavior of synovial fibroblasts in a bioinspired synovium-on-chip model - Susanna Piluso; Yang Li; Liliana Moreira Texeira; Prasanna Padmanaban; Jeroen Rouwkema; Jeroen Leijten; René van Weeren; Marcel Karperien; Jos Malda (Journal of Cartilage & Joint Preservation)
ABSTRACT: Introduction: Due to the loading of the articular joints and the movement of the joint itself, mechanical stress is constantly exerted on the synovial cavity, which is, in turn, reflected as shear stress toward the surrounding tissues, including the synovium. Although it is known that synovial cells are sensitive to various mechanical cues, deeper understanding on how synovial fibroblasts (SFBs) respond to increased shear stress is required to gain insights on its role in the pathophysiology of osteoarthritis (OA). Objectives: A synovium-on-chip model was developed to evaluate the effect of fluid flow-induced shear stress on fibroblast-like synoviocytes, and to assess the similarities with synovial inflammation during OA. Methods: Patient-derived SFBs were exposed to a shear stress of 3, 8, and 15 dyne/cm2 for up to 72 hours. Production of TNFα, IL-6, MMPs, and lubricin by synovial cells was analyzed. Results: The levels of TNFα, IL-6, and degradative enzymes increased over time when synovial cells were exposed to a shear stress of 8 dyne/cm2. In the first 8 hours, a 5-fold increase in the level of TNFα was observed when the shear stress increased from 3 to 8 dyne/cm2, and a 2-fold increase from shear stress 8 to 15 dyne/cm2. Conclusions: High mechanical stress combined with inflammatory triggers can cause excessive production of cytokines and proteolytic enzymes. Knowledge of how SFBs respond to increasing shear stress contributes to understanding the pathophysiology of OA, in which intra-articular pressure is often elevated, and may contribute to the discovery of potentially effective therapeutic agents.